مطبوعة مقياس القانون والتشريع الرياضي - تريش ، لحسن (Mohamed Boudiaf University of M'Sila, 2024)
الملخص : بالعربية : بشكل عام، يهدف التربية البدنية والرياضية إلى تعزيز صحة الجسم والعقل، وتطوير القدرات الحركية والمهارات الرياضية، وتعزيز النمو الشخصي والانضباط، وتعزيز الروح الرياضية والقيم الأخلاقية. يعتبر ممارسة النشاط البدني والمشاركة في الأنشطة الرياضية أمرًا هامًا للحفاظ على صحة جيدة وتحقيق التوازن الشامل في الحياة وفي هذا الصدد تتحدث المحاضرات القانونية والتشريعية في مجال الرياضة عن القوانين واللوائح التي تنظم النشاط الرياضي في الجزائر. يتم تناول عدة مواضيع مهمة خلال هذه المحاضرات. فيما يلي بعض المواضيع التي يمكن أن تُغطى في محاضرات القانون والتشريع الرياضي. . مدخل للقانون الرياضي يتم تقديم نظرة عامة على المفاهيم والمبادئ الأساسية للقانون الرياضي، بما في ذلك مفهوم الرياضة وأهدافها، وتنظيم الاتحادات والهيئات الرياضية. . التشريعات الرياضية في الجزائر يتم استعراض القوانين واللوائح المعمول بها في الجزائر لتنظيم النشاط الرياضي، بما في ذلك القوانين المتعلقة بتنظيم الهيئات الرياضية المحلية والوطنية. يتم التطرق إلى قواعد الانضباط الرياضة والعقوبات المفروضة على المخالفين، مثل الإيقافات والغرامات والعقوبات الأخرى، وكيفية تنفيذها.قضايا قانونية في الرياضة: يتم مناقشة بعض القضايا القانونية التي قد تنشأ في مجال الرياضة، مثل قضايا العنف الرياضي، التعاقدات بين الرياضيين والأندية، الرياضية، وغيرها من المسائل ذات الصلة. Searchlight in English In general, physical education and sports aim to promote physical and mental health, develop motor skills and athletic skills, promote personal growth and discipline, and enhance sportsmanship and moral values. Practicing physical activity and participating in sports activities is important for maintaining good health and achieving a comprehensive balance in life. In this regard, legal and legislative lectures in the field of sports talk about the laws and regulations that govern sports activity in Algeria. Several important topics are covered during these lectures. Here are some of the topics that can be covered in sports law and legislation lectures and this publication in which we will discuss . Introduction to sports law: An overview of the basic concepts and principles of sports law is provided, including the concept and objectives of sports, and the organization of sports federations and bodies. . Sports legislation in Algeria: The laws and regulations in force in Algeria to regulate sports activity are reviewed, including laws related to the organization of local and national sports bodies. Sports discipline rules and penalties for violators, such as suspensions, fines and other sanctions, and how to enforce them are addressed. Legal issues in sports: Some legal issues that may arise in the field of sports are discussed, such as sports violence, contracts between athletes and sports clubs, and other related issues.
Keywords: القانون الرياضي; التشريع الرياضي; تعزيز صحة الجسم